Ceremonial Time : Fifteen Thousand Years on One Square Mile - Mitchell, John Hanson (Book collections on Project MUSE., 2013)
A book that turns one modest square mile of exurban land into the most remarkably fascinating place. "Ceremonial time" occurs when past, present, and future can be perceived simultaneously. Experienced only rarely, usually during ritual dance, this escape from linear time is the vehicle for the author's extraordinary writing. He traces the life of a single square mile in New England, from the last ice age through years of human history, including bear shamans, colonists, witches, local farmers, and encroaching industrial "parks."